2013
DOI: 10.1007/s00436-013-3351-1
|View full text |Cite
|
Sign up to set email alerts
|

Further insecticidal activities of essential oils from Lippia sidoides and Croton species against Aedes aegypti L.

Abstract: This study assessed new insecticidal activities of essential oils from Lippia sidoides and Croton species (Croton zehntneri, Croton nepetaefolius, Croton argyrophylloides, and Croton sonderianus) against Aedes aegypti mosquito. In addition, the acute toxicity upon mice was determined. All essential oils showed inhibition of egg hatching, with IC50 values ranging from 66.4 to 143.2 μg mL(-1), larvicidal activity with LC50 ranging from 25.5 to 94.6 μg mL(-1), and pupicidal action with PC50 ranging from 276.8 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 21 publications
2
31
1
6
Order By: Relevance
“…(Verbenaceae), also known as "rosemary pepper" is an aromatic plant of popular medicinal use found in the Caatinga region of the Brazilian Northeast (Santos et al, 2016). It presents insecticidal activity against Tenebrio molitor (Lima et al, 2011) and larvae of Aedes aegypti (Lima et al, 2013) and acaricide against Tetranychus urticae Koch (Soares et al, 2016). When tested against different pathogenic bacteria, such as Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli (Ratnaweera et al, 2015) and different fungi and yeasts, including Candida albicans (Premjanu et al, 2016), it demonstrated a strong antimicrobial action.…”
Section: Introductionmentioning
confidence: 99%
“…(Verbenaceae), also known as "rosemary pepper" is an aromatic plant of popular medicinal use found in the Caatinga region of the Brazilian Northeast (Santos et al, 2016). It presents insecticidal activity against Tenebrio molitor (Lima et al, 2011) and larvae of Aedes aegypti (Lima et al, 2013) and acaricide against Tetranychus urticae Koch (Soares et al, 2016). When tested against different pathogenic bacteria, such as Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli (Ratnaweera et al, 2015) and different fungi and yeasts, including Candida albicans (Premjanu et al, 2016), it demonstrated a strong antimicrobial action.…”
Section: Introductionmentioning
confidence: 99%
“…Good examples are the larvicidal EOs obtained from Clausena anisata (Govindarajan 2010b), Coleus aromaticus (Govindarajan et al 2013b), Dalbergia sisoo (Ansari et al 2000a), Hyptis martiusii (Araujo et al 2003), Hyptis suaveolens (Sakthivadivel et al 2015), Lavandula gibsoni (Kulkarni et al 2013), Lippia sidoides (Lima et al 2013), Moschosma polystachyum (Rajkumar and Jebanesan 2004), Mentha spicata (Govindarajan et al 2012), Mentha piperita (Ansari et al 2000b), Mentha longifolia (Pavela et al 2014), Ocimum basilicum (Govindarajan et al 2013a), Ocimum selloi (Padilha de Paula et al 2003), Ocimum americanum (Tawatsin et al 2001), Ocimum gratissimum (Cavalcanti et al 2004), Ocimum sanctum (Gbolade and Lockwood 2008), Plectranthus barbatus ), Plectranthus ambonicus (Lima et al 2011), Plectranthus mollis (Kulkarni et al 2013), Pogostemon cablin (Trongtokit et al 2005), Pulegium vulgare (Pavela et al 2014), Rosmarinus officinalis (Prajapati et al 2005), Satureja hortensis (Pavela 2009), Tagetus minuta (Perich et al 1995), Thymus vulgaris (El-Akhal et al 2016), Thymus leucospermus, Thymus teucrioides (Pitarokili et al 2011), Vitex agnus castus (Cetin et al 2011), and others (Cheng et al 2003;Traboulsi et al 2005;Pavela et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre elas, destacam-se Piper marginatum (AUTRAN et al, 2009), Sapindus saponaria (BARRETO et al, 2006), Dendropanax morbifera (CHUNG et al, 2009), Citrus sinensis (EL-AKHAL et al, 2015), Copaifera reticulata (GERIS et al, 2008), Mentha piperita (KUMAR et al, 2011), Lippia sidoides (LIMA et al, 2013), Piper aduncum (OLIVEIRA et al, 2013), Anacardium humile (PORTO et al, 2008), dentre outras.…”
Section: Introductionmentioning
confidence: 99%